Perceptual reversals and creativity: is it possible to develop divergent thinking by modulating bistable perception? (2023)
The purpose of this article was to examine the relations that exist between bistable perception and divergent thinking, taking as a reference that flexibility emerges in both mechanisms, perceptually or cognitively. To achieve the objective, a literary review was carried out using six databases. The keywords used were: bistable perception, perceptual reversals, insight, creative cognition, creative flexibility, perceptual flexibility. 19 articles on the relationship between bistable perception, flexibility and creativity were found. 44 studies regarding both bistable perception and the mechanisms that are involved while cognitive flexibility emerges were considered. 2 reviews on bistable perception were also included. 6 articles related to creativity as a cognitive phenomenon were collated, plus another 3 on perceptual processes. After having made the analysis, it is concluded that the modulating mechanisms of bistable perception have a possibility of being incorporated to develop creativity from perceptual reconfiguration processes that involve flexibility mechanisms.